Evaluation of Drug Information Services in a Tertiary Care Hospital - Inamdar, Syed Zia; Londhe, Sushil Kumar; Kategri, Sumanyu; Kulkarni, Raghavendra; Badiger, Sharan; Biradar, Siddanagouda (Indian Journal of Pharmacy Practice)
Drug information services are of prime importance in delivering optimal drug therapies by providing specific and unbiased information to healthcare professionals. Present work has been undertaken to evaluate the pattern of various drug information queries received by the drug information center in a tertiary care hospital. A total of 593 drug information queries that were received during the period were evaluated retrospectively. Upon assessment, it was found that most of the beneficiaries of the service were physicians (51%). Greater numbers of queries received were to update knowledge (71.27%), followed by better patient care (28.72%). Most of the queries are received during ward rounds (71.63%). The types of queries received were categorically related to drug profile (6.75%), dosage information (3.71%), drug indication (13.49%), adverse effects (21.42%), the pharmacokinetics of drug (3.37%), pharmacotherapy (4.05%), drug interactions (1.52%), mechanism of action (11.30%), pharmacotherapy (4.05%) and poison information (0.17%). The source of reference for response to the query is mainly electronic databases (50.59%), secondary (21.08%), and tertiary sources (16.86%). The drug information services provided by the pharmacy practice cater to the healthcare services’ needs for better patient care and updated knowledge. Moreover, these services will help the medical professional to prefer appropriate medicine in the management of the disease, thereby improving the treatment outcomes and patients’ quality of life.
Keywords: Drug Information; Drug Information Services; Drug Query; Knowledge Update